Targeted Adherence Intervention to Reach Glycemic Control with Insulin Therapy for patients with Diabetes (TARGIT-Diabetes): rationale and design of a pragmatic randomised clinical trial - Lewey, Jennifer (BMJ Open, 2017)
INTRODUCTION: Adherence to and persistence of medications for chronic diseases remains poor and many interventions to improve medication use have only been modestly effective. Targeting interventions to patients who are most likely to benefit should improve their efficiency and clinical impact. This study aims to test the impact of three cost-equivalent pharmacist-led interventions on insulin persistence and glycaemic control among patients with diabetes. METHODS AND ANALYSIS: TARGIT-Diabetes (Targeted Adherence Intervention to Reach Glycemic Control with Insulin Therapy for patients with Diabetes) is a randomised controlled trial that will evaluate three different multifaceted pharmacist-outreach strategies for improving long-term insulin use among individuals with diabetes. We will randomise 6000 patients in a large insurer to one of three arms. The arms are designed to deliver an increasingly intensive intervention to a progressively targeted population, identified using predictive analytics. The central component of the intervention in all arms is a tailored telephone consultation with a pharmacist which varies across arms based on the: (A) proportion of patients offered the intervention and (B) intervention intensity, including follow-up frequency and cointerventions such as text reminders and interactions with patients’ providers. The primary outcome is insulin persistence, assessed using pharmacy claims data, and the secondary outcomes are glycaemic control as measured by glycosylated haemoglobin values, healthcare utilisation and healthcare spending. ETHICS AND DISSEMINATION: This protocol has been approved by the Institutional Review Board of Brigham and Women’s Hospital and the Privacy Board of Horizon Blue Cross Blue Shield of New Jersey. We plan to present the results of this trial at national meetings and in manuscripts submitted to peer-reviewed journals. TRIAL REGISTRATION NUMBER: NCT 02846779.